Fibromyalgia simple relief through movement - Bigelow, Stacie L. (John Wiley& sons, 2000)
This caring and knowledgeable guide can help you feel better--starting now Fibromyalgia causes muscle stiffness and pain, debilitating fatigue, and numerous other symptoms. Most frustrating of all, people with fibromyalgia syndrome don't look sick; standard tests for injury or chemical imbalances often show nothing wrong.